The influence of destination experience on destination loyalty in an emerging economy - Taskeen ud Din; Saman Attiq; Moin Ahmed Moon (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Destination loyalty has gained prominence because of the growing competition among tourist destinations. This study aims to test the influence of destination experiences (experience authenticity and experience quality) on destination loyalty. Further, tourist engagement was tested as a mediator between destination experiences and loyalty. Survey data were collected onsite from 600 random tourists visiting the Swat and Chitral districts of Khyber-Pakhtunkhwa province in Pakistan and analyzed through structural equation modeling techniques using Smart PLS 3.9 software. Experience authenticity is the stronger antecedent of destination loyalty. Furthermore, the relationship between destination experience component and destination loyalty is mediated by tourist engagement. This study differentiates between extraordinary and ordinary destination experiences, represented by experience authenticity and experience quality. A theoretical network was validated, connecting destination experience, tourist engagement and destination loyalty. Destination management organizations can use this model to coordinate the efforts of attractions, service providers and tourists to co-create optimal destination experience.
Keywords: 330; tourist engagement; experience authenticity; experience quality; interactionquality; physical environment quality; destination loyalty; Pakistan